Pricing and hedging interest and credit risk sensitive instruments - Skinner, Frank, 1957- (Oxford [England] ; Burlington, MA : Elsevier Academic Press, 2005)
This book is tightly focused on the pricing and hedging of fixed income securities and their derivatives. It is targeted at those who are interested in trading these instruments in an investment bank, but is also useful for those responsible for monitoring compliance of the traders such as regulators, back office staff, middle and senior lever managers. To broaden its appeal, this book lowers the barriers to learning by keeping math to a minimum and by illustrating concepts through detailed numerical examples using Excel workbooks/spreadsheets on a CD with the book. On the accompanying CD with the book, three interest rate models are illustrated: Ho and Lee, constant volatility and Black Derman and Toy, along with two evolutionary models, Vasicek and CIR and two credit risk models, Jarrow and Turnbull and Duffie and Singleton. These are implemented via spreadsheets on the CD. * Starts at an introductory level and then develops advanced topics * Provides plenty of numerical examples rather than mathematical equations to aid full understanding of the strengths and weaknesses of all interest rate derivative models * Can be used for self-study - a complete book on the topic, which includes examples with answers.
An Introduction to Interest Rate and Credit Sensitive Instruments; The Sovereign Term Structure and the Risk Structure of Interest Rates; Measuring the Existing Sovereign Term Structure and the Risk Structure of Interest Rates; Modelling the Sovereign Term Structure of Interest Rates: The Binomial Approach; Interest Rate Modelling: The term structure consistent approach; Interest and Credit Risk Modelling; Hedging Sovereign Bonds: The Traditional Approach; Active and Passive Strategies; Alternative Hedge Ratios; Pricing and Hedging Non-Fixed Income Securities; Credit Derivatives; Embedded Options.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Hedging (Finance).; Interest rates -- Mathematical models; Credit -- Management -- Mathematical models; Risk management -- Mathematical models; Electronic books